Sex Education Based on the Philosophical Paradigm for Adolescens: Challenges and Strategies for Preventing Free Sex in the Digital Era - Maulia, Zahrotul; Ulfa, Maria; Mahardika, I Ketut; Waluyo, Joko; Soepeno, Bambang (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This study aims to determine the role of sex education for adolescents, challenges, strategies, and philosophical paradigms of sex education. This research was conducted based on a qualitative approach using a systematic literature review method. The analysis was conducted by synthesizing journals (both international and national) that discuss sex education for adolescents by examining the title, year of reference, author, content, and discussion of the references. he results of this research are; 1. The main role of sex education is to equip adolescents with values ​​that will help them in making good and responsible decisions regarding their sexuality and mitigate practice of free sex; 2) The digital era has brought a number of negative impacts, one of the is the ease children access content that is not appropriate for their age, including pornographic sites; 3) Parents, teachers and health worker have a major contribution in providing sex education.; 4) The philosophy of sex is discussed conceptual and moral questions, such as the nature of sexual desire, sexual orientation, sexual activity, the morality of sexual acts, the morality of various sexual practice.